2016
DOI: 10.1097/iae.0000000000001325
|View full text |Cite
|
Sign up to set email alerts
|

Hyperspectral Autofluorescence Imaging of Drusen and Retinal Pigment Epithelium in Donor Eyes With Age-Related Macular Degeneration

Abstract: Purpose To elucidate the molecular pathogenesis of age-related macular degeneration (AMD) and interpretation of fundus autofluorescence (AF) imaging, we identified spectral AF characteristics of drusen and retinal pigment epithelium (RPE) in donor eyes with AMD. Methods Macular RPE/Bruch’s membrane (BrM) flat mounts were prepared from 5 donor eyes with AMD. In 12 locations (1–3/eye), hyperspectral AF images in 10-nm-wavelength steps were acquired at 2 excitation wavelengths (λex 436 nm, 480 nm). A non-negati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
70
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 59 publications
(65 reference statements)
7
70
1
Order By: Relevance
“…This confirms earlier studies that found shorter emission peak wavelengths for sub-RPE deposits, drusen, and Bruch's membrane compared to RPE in confocal microscopy of histologic sections of donor eyes. 19,20 Also, widefield epifluorescence microscopy of RPE/Bruch's membrane flat mounts showed shorter emission wavelengths for drusen than for the RPE. 20 Nonnegative tensor factorization 21 revealed a drusen-specific spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…This confirms earlier studies that found shorter emission peak wavelengths for sub-RPE deposits, drusen, and Bruch's membrane compared to RPE in confocal microscopy of histologic sections of donor eyes. 19,20 Also, widefield epifluorescence microscopy of RPE/Bruch's membrane flat mounts showed shorter emission wavelengths for drusen than for the RPE. 20 Nonnegative tensor factorization 21 revealed a drusen-specific spectrum.…”
Section: Discussionmentioning
confidence: 99%
“…The major fluorophores of the human macula are thus currently unknown and are subject to research (Tong et al. ). In vivo lipofuscin is excited by wavelengths of light ranging from 400 to 590 nm, with a peak between 490 and 510 nm.…”
Section: Introductionmentioning
confidence: 99%
“…Fundus autofluorescence (AF) of lipofuscin has long been thought to originate from bisretinoid fluorophores in the RPE cells, particularly A2E Yamamoto et al 2012), but more recently this most studied bisretinoid (and hence its derivatives) has been found in low quantities in the macula of humans (Ablonczy et al 2013). The major fluorophores of the human macula are thus currently unknown and are subject to research (Tong et al 2016). In vivo lipofuscin is excited by wavelengths of light ranging from 400 to 590 nm, with a peak between 490 and 510 nm.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, other components of cells, including flavin adenine dinucleotide (FAD), nicotinamide adenine dinucleotide phosphate (NADPH), and the carotenoids zeaxanthin and lutein, have weak fluorescence in the same spectral area as LGs [7][8][9]. In addition, spectral autofluorescence characteristics of drusen have been observed in donor eyes with AMD [10].…”
Section: Introductionmentioning
confidence: 99%